Utility of Physiologically Based Modeling and Preclinical In Vitro/In Vivo Data to Mitigate Positive Food Effect in a BCS Class 2 Compound - Xia, Binfeng (Springer US, 2013)
Physiologically based pharmacokinetic (PBPK) modeling has become a useful tool to estimate the performance of orally administrated drugs. Here, we described multiple in silico/in vitro/in vivo tools to support formulation development toward mitigating the positive food effect of NVS123, a weak base with a pH-dependent and limited solubility. Administered orally with high-fat meal, NVS123 formulated as dry filled capsules displayed a positive food effects in humans. Three alternative formulations were developed and assessed in in vitro and in vivo preclinical and/or clinical studies. By integrating preclinical in vitro and in vivo data, the PBPK model successfully estimated the magnitude of food effects and the predicted values were within ±30% of the observed results. A model-guided parameter sensitivity analysis illustrated that enhanced solubility and longer precipitation times under fed condition were the main reason for enhanced NVS123's exposure in presence of food. Eventually, exposure after an amorphous formulation was found to be not significantly altered because of remarkably enhanced intestinal solubility and reduced precipitation. Gastroplus population simulations also suggested that the amorphous formulation is promising in mitigating a clinically significant food effect. Overall, these efforts supported the rationale of clinical investigation of the new formulation, and more importantly, highlighted a practical application of PBPK modeling solving issues of undesirable food effects in weakly basic compounds based on preclinical in vitro/in vivo data. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1208/s12249-013-0018-2) contains supplementary material, which is available to authorized users.